The effect of traffic applications on travel behaviour - Bakioğlu, Gözde. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Traffic information has been in uenced the choice behavior of travelers while en route. The main goal of this study is to investigate the impact of real-time traffic information acquired through some traffic applications such as GPS navigation devices for car, mobile traffic applications and radio traffic reports on traveler behavior on highways. This study estimates binary logit mode choice model of the decision making for travel of people stayed at the civil engineering faculty of Istanbul Technical University. Commuter responses to traffic information were analysed seperately in two di erent commuters mode, including self-driving commute and public transit commute by using Binary Logit Model. The travel behaviour models developed in this study are based on a self deviced survey of travelers which was conducted for the civil engineering undergraduate-graduate students, academicians and supporting sta at Istanbul Technical University, Istanbul, in 2016. The attributes that in uence travelers' decision-making patterns can be broadly categorized into three groups which were socioeconomics, travel and technological characteristics. Moreover, travelers who obtain traffic information from some traffic applications were more likely to switch with respect their di erent characteristics. In addition, a variety of features of all traffic applications obtained from some related websites were also analysed. There are some di erence regarding their signi cant variables and their descriptive statistic results between traffic applications that use in Turkey and in the world. In this study, each traffic application were also analysed and compare them in terms of their categorical attributes with the help of developing regression model. The purpose of this analysis is to investigate the index of the rating of the traffic applications used in Turkey and in the world. Further outcomes were presented related to findings.
Keywords: Global Positioning System.; Traffic management.